2020
DOI: 10.17581/bp.2020.09202
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of anther development in flowering plants

Abstract: The analysis showed that when studying the anther of flowering plants there is a comp lex of unsolved embryological problems. First of all, they relate to the first stages of microsporangium initiation and time of archesporium differentiation. Many of classifications of microsporangium wall formation were worked out on the base of parietal tissue formation features. Of the 4 types of microsporangium wall formation proposed by Davis (1966), 2 types (basic and reduced) are contro ver sial. In the classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The high level of variability of the trait allows the assumption that the trait is under strong selection pressure. The number of carpels and ovules, on the other hand, is strictly determined by genotype [20,21]. A number of researchers [22,23] found that one of the reasons of lower seed productivity is abnormalities in embryonic development.…”
Section: Resultsmentioning
confidence: 99%
“…The high level of variability of the trait allows the assumption that the trait is under strong selection pressure. The number of carpels and ovules, on the other hand, is strictly determined by genotype [20,21]. A number of researchers [22,23] found that one of the reasons of lower seed productivity is abnormalities in embryonic development.…”
Section: Resultsmentioning
confidence: 99%
“…Las principales características analizadas en los granos de polen se resumen en la Tabla 2. DISCUSIÓN La pared de las anteras maduras de T. cacao presenta una epidermis persistente, un endotecio con engrosamientos fibrilares que se encuentra recubierto por restos de las paredes tapetales, este patrón histológico básico, es común en las anteras maduras y dehiscentes de la mayoría de las angiospermas (Passarelli & Cocucci, 2006;Wilson, Song, Taylor, & Yang, 2011;Wei, Xu, & Li, 2015;Shamrov, Anisimova, & Babro, 2020), incluido Malvaceae (Tang, Gao, Wang, & Chen, 2006;Galati, Monacci, Gotelli, & Rosenfeldt, 2007;Tang, Gao, & Xie, 2009;Lattar, Galati, & Ferruci, 2014). Concordando con las observaciones de Manning (1996), los engrosamientos fibrilares presentes en el endotecio de los genotipos de T. cacao son el tipo anular y es similar a lo registrado para varias especies dentro de la familia Malvaceae (Lattar et al, 2014); aunque no son exclusivos de este grupo de plantas (French, 1985;Manning & Linder, 1990;Manning, 1996;Tebbitt & Maciver, 1999;Carrizo, 2002;Nakamura, Longhi-Wagner, & Scatena, 2010;Gotelli, Galati, & Zarlavsky, 2016).…”
Section: Resultsunclassified
“…As our studies have shown, the reduced as well as the basic types are variations of the centripetal type: the basic type is included in a complicated variation, while the reduced type is a modification of the typical variation (Shamrov et al, 2020). In some flowering plants (Allium caspium (Pall.)…”
Section: Introductionmentioning
confidence: 91%
“…An analysis of the available data indicates that in plants with the basic and dicotyledonous types of microsporangium wall formation (according to Davis, 1966), fibrous thickenings are formed not only in the subepidermal, but also in the remaining underlying layers. Consequently, the formation of multi-layered endothecium is characteristic of complicated variations of both centrifugal and centripetal types, proposed by Shamrov et al (2020). Plants with flowers developing in water in the case of hyphydrogamy (Ceratophyllaceae, Cymodoceae, Najadaceae, Hydrocharitaceae) and species with cleistogamous flowers lack fibrous thickenings in the microsporangium wall (Fig.…”
Section: Chacteristics Of Microsporangium Wall Layersmentioning
confidence: 99%
See 1 more Smart Citation